The Effect of Assurance Report, Public Ownership, and Slack Resources on Quality of CSR Disclosure in Indeks Saham LQ45 2017-2020 - Annisa Andi Setyani; Willy Sri Yuliandhari (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2022)
This study aims to determine the effect of assurance reports, public ownership, and slack resources on the quality of CSR disclosure on the 2017-2020 LQ45 index. The sampling technique used purposive sampling technique, where 17 samples were obtained with observations for four years, so there were 68 observational data from companies listed in the LQ45 index from 2017-2020. The analytical method used is descriptive statistical analysis and panel data regression using Eviews 12. The results of this study are assurance reports, public ownership, and slack resources simultaneously affect the quality of CSR disclosure on the 2017-2020 LQ45 index. Partially, only assurance reports have a positive influence on the quality of CSR disclosure on the 2017-2020 LQ45 index. Meanwhile, public ownership and slack resources have no effect on the quality of CSR disclosure on the 2017-2020 LQ45 index.